UJI ORGANOLEPTIK KERUPUK SUSU DENGAN PENAMBAHAN TEPUNG TAPIOKA - Ayu Dwi Sari; Nita opi ari kustanti; Resti Yuliana Rahmawati (Universitas Islam Balitar, 2021)
This The purpose of this study was to determine the effect of mixing tapioca flour on organoleptik test (color,taste,aroma,crispness) on cow’s milk crackers. The research method is an experiment a completely randomized design (CRD) with a unidirectional pattern. The treatment in this study was the use of tapioca flour on cow’s milk which consisted of 5 treatment, namely the addition of 750 gr, 700 gr, 650 gr, 600 gr where each treatment was repeated 5 times. The results of this study were the organoleptic effect of tapioca flour and the addition of cow’s milk on the resulting milk crackers, namely the best treatmen was the color in the treatment (P3) yellowish white, the taste in the treatment (P4) did not taste milky, the aroma in the treatment (P4) was quite milky, The crispness in treatment (P4) was quite crunchy. However, it is better to make cow's milk crackers by mixing tapioca flour more so that the taste and aroma of cow's milk crackers are better. From the conclusion for P3 treatment (with the addition of 700gram tapioca flour).